Low serum selenium in pregnancy is associated with reduced T3 and increased risk of GDM. Issue 1 (January 2021) - Hofstee, Pierre; James-McAlpine, Janelle; McKeating, Daniel R; Vanderlelie, Jessica J; Cuffe, James S M; Perkins, Anthony V
Abstract : Thyroid disorders are the most common endocrine disorders affecting women commencing pregnancy. Thyroid hormone metabolism is strongly influenced by selenium status; however, the relationship between serum selenium concentrations and thyroid hormones in euthyroid pregnant women is unknown. This study investigated the relationship between maternal selenium and thyroid hormone status during pregnancy by utilizing data from a retrospective, cross-sectional study (Maternal Outcomes and Nutrition Tool or MONT study) with cohorts from two tertiary care hospitals in South East Queensland, Australia. Pregnant women ( n = 206) were recruited at 26–30 weeks gestation and serum selenium concentrations were assessed using inductively coupled plasma mass spectrometry. Thyroid function parameters were measured in serum samples from women with the lowest serum selenium concentrations (51.2 ± 1.2 µg/L), women with mean concentrations representative of the entire cohort (78.8 ± 0.4 µg/L) and women with optimal serum selenium concentrations (106.9 ± 2.3 µg/L). Women with low serum selenium concentrations demonstrated reduced fT3 levels ( P < 0.05) and increased TPOAb ( P < 0.01). Serum selenium was positively correlated with fT3 ( P < 0.05) and negatively correlated with TPOAb ( P < 0.001). Serum fT4 and thyroid-stimulating hormone (TSH) were not different between all groups, though the fT4 /TSH ratio was increased in the low selenium cohort ( P < 0.05). Incidence of pregnancy disorders, most notably gestational diabetes mellitus, was increased within the low serum selenium cohort ( P < 0.01). These results suggest selenium status in pregnant women of South East Queensland may not be adequate, with possible implications for atypical thyroid function and undesirable pregnancy outcomes.